The C/EBPβ antagonist peptide lucicebtide (ST101) induces macrophage polarization toward a pro-inflammatory phenotype and enhances anti-tumor immune responses - Claudio Scuoppo; Rick Ramirez; Siok F. Leong; Mark Koester; Zachary F. Mattes; Karen Mendelson; Julia Diehl; Franco Abbate; Erin Gallagher; Lila Ghamsari; Abi Vainstein-Haras; Gene Merutka; et al. (Frontiers in Immunology, 2025)
Immune-checkpoint inhibitors (ICIs) have shown unprecedented success in a subset of immunogenic tumors, however a host of patients with advanced solid tumors fail to respond well or at all to immunotherapy. Refractory tumors commonly display a tumor microenvironment (TME) rich in immunosuppressive macrophages (M2-like) that suppress adaptive immunity and promote tumor progression. The ability to reprogram macrophages in the TME into an immune-active state holds great promise for enhancing responses to ICIs. Lucicebtide (previously referred to as ST101) is a peptide antagonist of the transcription factor C/EBPβ, a key activator of the transcriptional program in immunosuppressive macrophages. Here we show that lucicebtide exposure reprograms human immunosuppressive M2-like macrophages to a pro-inflammatory M1-like phenotype, restores cytotoxic T cell activation in immunosuppressed co-culture assays in vitro, and further increases T-cell activity in M1-like/T cell co-cultures. In immunocompetent, macrophage-rich triple-negative breast and colorectal cancer models, lucicebtide induces repolarization of tumor-associated macrophages (TAMs) to a pro-inflammatory M1-like phenotype and suppresses tumor growth. Lucicebtide synergizes with anti-PD-1 therapy and overcomes resistance to checkpoint inhibition in anti-PD-1-refractory tumors, but in vivo responses are impaired by systemic macrophage depletion, indicating that macrophage reprogramming is integral to lucicebtide activity. These results identify lucicebtide as a novel immunomodulator that reprograms immunosuppressive macrophage populations to enhance anti-tumor activity and suggests its utility for combination strategies in cancers with poor response to ICIs.